A Straightforward and High-Yielding Synthesis of 1, 2, 4-Oxadiazoles from Chiral N-Protected α-Amino Acids and Amidoximes in Acetone-Water: An Eco-Friendly Approach. (16th January 2019) - Sauer, André C.; Wolf, Lucas; Quoos, Natália; Rodrigues, Mariele B.; Braga, Antônio L.; Rodrigues, Oscar E. D.; Dornelles, Luciano
Abstract : A straightforward and high-yielding methodology for the synthesis of a high structural diversity of 1, 2, 4-oxadiazoles from different chiral N -protected α -amino acids and amidoximes under microwave (MW) irradiation is described herein. This greener approach gives the desired products using acetone/water as solvent in very short reaction times.